2013
DOI: 10.1016/j.enbuild.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Cool roof technology in London: An experimental and modelling study

Abstract: One of the primary reasons for the application of cool materials is their energy and associated environmental impact on the built environment. Cool materials are usually applied on the roof of buildings to reduce cooling energy demand. The relative benefits of this reduction depend on the construction of the building, external weather conditions and use of the building. This paper examines the impact from the application of a reflective paint on a flat roof in a naturally ventilated office building in the area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(65 citation statements)
references
References 15 publications
6
55
0
4
Order By: Relevance
“…The majority of those researches calculates the increased heating demand through energy and microclimatic simulations [21,28,31,33,36,38]; some authors, such as Kolokotroni et al [33], Stavrakakis et al [38] and Pisello et al [37] have performed on-site monitoring of some variables mainly to validate the building simulation model. Finally, some researches analyse the energy performances of cool roofs though a comparative assessment with respect to green roofs [28], or balance cooling savings with the increasing of the heating consumptions in winter [28,35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of those researches calculates the increased heating demand through energy and microclimatic simulations [21,28,31,33,36,38]; some authors, such as Kolokotroni et al [33], Stavrakakis et al [38] and Pisello et al [37] have performed on-site monitoring of some variables mainly to validate the building simulation model. Finally, some researches analyse the energy performances of cool roofs though a comparative assessment with respect to green roofs [28], or balance cooling savings with the increasing of the heating consumptions in winter [28,35].…”
Section: Resultsmentioning
confidence: 99%
“…Many other authors have instead analysed and demonstrated the effectiveness and the benefits of adopting cool roofs to reduce the energy consumptions of buildings for summer cooling in different climates [9,20,23,[26][27][28][29][30][31][32], considering buildings with different end uses [29,31,33,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased the reflection effect more than 88%. To take advantage of the positive effect of cooled roof technology and decrease the cooling energy consumption in summer [15,16], the coating was used to cover the entire roof. Since in OFFICE projects for these types of buildings in all climates the potential decrease in lighting energy use is limited [12], the angle of the reflectors was modified to produce the best possible effect.…”
Section: Methodsology and Retrofitting Scenariosmentioning
confidence: 99%
“…The reflectivity varies from about 0.1 for a very black colours to 0.8 for a very white colour. Generally, the rejection of solar gain is the main goal of passive cooling strategies [38] especially in hot climates. Direct sunlight onto a roof not only affects the indoor thermal comfort; thermal radiation coming from the roof materials affects the micro climate around a building [5].…”
Section: Solar Reflection Of the Roof Surfacementioning
confidence: 99%